Market failures as premises of granting state aid - Bartosz Bartniczak (Economic and Environmental Studies (E&ES), 2017)
Economists from centuries have been leading discussions on the role of state in economy. Some of them are in favour of state's wide interference in economy while others seek to limit the role of the government. One of the arguments for the necessity of state interventionism in the market mechanism is the existence of market failures. However interfering in the market without any restrictions could lead to much greater disturbances than those causing market failures. Therefore significant restrictions are placed on the role of the state in economy. In the European Union a policy of state aid is introduced, which shows when and for what purposes state support may be granted. The main aim of this article is to show how state aid influences on the market failures' elimination. Provision of state aid is therefore justified by the presence of market failures.
Keywords: H23; H41; 330; state aid; market failures; equilibrium